1989
DOI: 10.5980/jpnjurol1989.80.167
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the Effects of Intravesical Bacillus Calmette-Guerin (Tokyo 172 Strain) Therapy for Superficial Bladder Cancer

Abstract: In this paper, we summarize the results of a multicentric controlled study of induction treatment with intravesical BCG in patients with superficial bladder cancer (Ta, T1) or CIS. The BCG Tokyo 172 strain (Japan BCG K.K.) was given for 8 weeks, as a rule, in a dose of either 80 mg or 120 mg in 40 ml of saline instilled into the bladder. Sixty-six (90.5%) of the 73 patients registered in the study were evaluable for response. High response rates were obtained in the patients with Ta or T1 tumors, irrespective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…(20) Despite good clinical efficacy, intravesical BCG instillation raises some serious problems such as frequent occurrence of various adverse effects. Akaza et al (5) observed bladder irritation symptoms in 69%, fever in 43.7% and macroscopic hematuria in 31%. Infrequent but severe adverse effects have also been reported (6), making it necessary to define the optimal BCG instillation method to improve safety while maintaining its efficacy.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…(20) Despite good clinical efficacy, intravesical BCG instillation raises some serious problems such as frequent occurrence of various adverse effects. Akaza et al (5) observed bladder irritation symptoms in 69%, fever in 43.7% and macroscopic hematuria in 31%. Infrequent but severe adverse effects have also been reported (6), making it necessary to define the optimal BCG instillation method to improve safety while maintaining its efficacy.…”
Section: Discussionmentioning
confidence: 96%
“…Akaza et al (12) reported that after the treatment of CIS of the bladder with BCG (Tokyo 172 strain) instillation at a dose of 80 mg once weekly for eight consecutive weeks, 27 of the 32 patients (84%) achieved CR. Although the optimal dose of the Tokyo 172 strain had been determined by previous clinical studies (5), we anticipated that it would be possible to reduce the instillation dose, given that the BCG Tokyo 172 strain is more potent [269.91 -28.64 • 10 6 c.f.u. (colony-forming units)/mg] than other strains (13), indicating that equipotent efficacy can be attained even at half of its standard dose (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dose was selected on the basis of results of extensive studies by Akaza et al [12][13] In some cases treatment was terminated before the course of six instillations could be performed, but all patients received at least three. The patients were asked to refrain, if possible, from urination within 2 h of the instillation and were monitored for bladder irritation, temperature change, and other clinical symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to its use as a tuberculosis vaccine, BCG is intravesically infused in non-muscle invasive bladder cancer patients. The therapeutic rate is more than 70% and is significantly higher than that of ICIs [ 118 , 119 ]. However, patients suffer from a high frequency of serious side effects due to the use of the live mycobacterium [ 120 ].…”
Section: Development Of a Lipid-based Nano Dds Of Use In Cancer Immunmentioning
confidence: 99%